75.7k views
2 votes
Y= x - 4
5x+y=-34
How would I do this in steps ?

User Jansma
by
4.8k points

1 Answer

3 votes

Answer:

x = -5 y = -9

Explanation:

y = x -4

5x + y = - 34

substitute x-4 in for y to solve for x

5x + x - 4 = 34

solve for x . . . add 5x + x = 6x

so you now have 6x-4 = -34

add 4 to both sides of the equation

6x-4 + 4 = -34+ 4

6x = -30

divide both sides by 6

6x/6 = -30/6

x= -5

then you plug -5 for x in the first equation

y = x - 4

y= -5 -4

y =-9

x= -5 y= -9

User Michael Wallasch
by
4.6k points